Meaning in life as a mediator of dark triad with confidence in treatment and subjective evaluation of treatment outcome among male drug abstainers - Shi, Liping; Sun, Shijin; Zhu, Xueli; Geng, Yaoguo (Frontiers in Psychiatry, 2022)
Background Although the roles of personality in predicting substance abuse have been widely documented, few studies have investigated the relationships the dark triad (DT) personalities had with confidence in treatment (CIT) and subjective evaluation of treatment outcome (SETO) in drug abstainers. Objective This study examined the relationship between DT and treatment-relevant variables, and the potential effect of meaning in life (MIL) in these links. Methods Participants were male inpatients who started substance abuse treatment between June and December 2018 in Henan Province, China. The inclusion criteria were the diagnosis of substance use disorders. The exclusion criteria were illiteracy, comorbidity with psychopathology disorders, intellectual disability, and refusal of consent. A total of 236 men (aged 21–62 years, M = 45.30, SD = 7.72) were randomly selected and reported their DT, MIL, CIT, and SETO. Results Results showed that DT was negatively correlated with MIL, CIT, and SETO. MIL was positively correlated with CIT and SETO. The dark triad is associated with CIT both directly and indirectly via MIL. DT is indirectly correlated with SETO via MIL. Higher levels of DT in drug abstainers can reduce CIT and SETO by decreasing individual's MIL. Conclusion This study provides insights into the links between the DT and treatment-relevant variables, which can potentially impact the effectiveness of current substance abuse treatment programs.